Evaluating the Effectiveness of Cybercounseling Interventions for Social Anxiety - Zulfa, Nadhifatuz; Farmawati, Cintami; Mufida, Mariya; Akmala, Firda; Rizqi, Arina (Bulletin of Counseling and Psychotherapy, 2024)
Social anxiety is a prevalent mental health issue in modern society, significantly affecting the quality of life of those impacted. However, access to mental health services, including traditional counseling, is often limited by various factors. This study aims to evaluate the effectiveness of a cybercounseling application in addressing social anxiety. The application, developed as part of this research, provides clients with the ability to consult counselors without the constraints of distance and time. Key features include real-time chat with counselors, mental health articles as "self-help" resources, and a tool for measuring social anxiety levels. This research follows a Research and Development (RnD) design, comprising three stages of testing: (1) expert validation, which confirmed the model as valid for use; (2) limited empirical testing, where the application showed significant effectiveness in reducing social anxiety based on Wilcoxon statistical tests (p < 0.05); and (3) large-scale testing, which further confirmed the application's effectiveness with similar significant results (p < 0.05). These findings suggest that the cybercounseling application is a viable tool for treating social anxiety in the digital era.